Scratch 2.0 game development hotshot : 10 engaging projects that will teach you how to build exciting games with the easy-to-use Scratch 2.0 environment - Pul, Sergio van (Packt Pub., 2014)
An easy-to-use book, containing 10 engaging projects that will help you learn how to build video games with the easy to use Scratch 2.0 environment. If you are a new, or current Scratch user and would like to improve your understanding of the new Scratch 2.0 interface, and learn how to make video games, this book is ideal for you. Each project is explained in-depth from start to finish, so everyone can follow along, even if you don't have much previous experience with the software. If you want to become a video game designer, this book is an easy- to- use and friendly guide about the world of i.